Effect of wire mesh structure parameter on the flame propagation characteristics of syngas explosion. (15th February 2023) - Cao, Xingyan; Wang, Zhi; Wang, Yue; Wang, Zhirong; Zhou, Yangqing
Highlights: Effect of mesh structure on explosion characteristics was researched by experiment. Relationship between explosion parameter at wire mesh two ends was analyzed deeply. Effect and mechanism of wire mesh structure on explosion intensity were clarified. Effect of wire mesh structure on flame temperature of its two ends was researched. Effective suggestion was proposed based on the research for practical application. Abstract: The effect of wire mesh structure parameter on the flame propagation characteristics and intensity of syngas explosion was studied by the visual experiment. The corresponding relationship between the flame propagation and pressure rise of wire mesh two ends under the flame resistance success and failure conditions was analyzed by the comparison. Results indicate that the wire mesh could effectively inhibit the explosion flame propagation and its structure parameter had a great influence on the explosion parameters of wire mesh two ends. As the flame resistance failed, the flame could be greatly accelerated after passing through the wire mesh. And the explosion pressure and flame propagation velocity of wire mesh upper end was obvious higher than those of lower end. As the wire mesh number and layer increased, the explosion intensity was decreased ceaselessly and the inhibition effect was enhanced gradually. For instance, the syngas explosion flame could be completely inhibited under 30 layer and 40 mesh numbers as c =  30 %. Δ P max were decreased respectively by 81.48 % and 65.52 % at the upper and lower ends of wire mesh. The pressure was greatly reduced as the flame resistance was successful. Especially the reduction in the flame temperature at the upper end of wire mesh. And the temperature did not reach the ignition temperature of syngas. The explosion inhibition was mainly attributed to the combination of the endothermic action and wall effect.